Aparelho Herbst x osteotomia sagital mandibular bilateral no tratamento do padrão II, classe II, divisão 1 em adultos: relato de casos - Schwartz, João Paulo [UNESP]; Kameyama, Daniela Cristina [UNESP]; Ravel, Taísa Boamorte; Sampaio, Luana Paz; Raveli, Dirceu Barnabé [UNESP] (My University, 2013)
Two treatment options are available for adult patients with skeletal Class II malocclusion caused by mandibular deficiency: combined mandibular advancement surgery and orthodontic treatment or mandibular advancement appliance. This study aimed to analyze the effects of two therapeutic modalities of Class II malocclusion treatment with mandibular deficiency. Two distinct individuals with Class II malocclusion division 1 and mandibular deficiency were treated after growth spurt. The first individual used the Herbst appliance as a therapeutic option and the second individual was treated with bilateral sagittal osteotomy. The cephalometric, occlusion and face results were evaluated for both individuals. Correction of Class II malocclusion was observed on both Herbst and surgery patients resulting on a normal occlusal relationship with normal overjet and overbite. Therefore it was concluded that Herbst appliance can be used to treat borderline skeletal Class II in adult patients.

Indivíduos adultos de Padrão II com deficiência mandibular e má oclusão de Classe II, divisão 1 possuem duas opções de tratamento: preparo ortodôntico com vistas à cirurgia de avanço mandibular ou aparelhos protratores mandibulares. O objetivo deste estudo foi analisar os efeitos de duas modalidades terapêuticas no tratamento da má oclusão de Classe II com deficiência mandibular. Dois indivíduos distintos com má oclusão de Classe II, divisão 1 e deficiência mandibular sagital foram tratados após o surto de crescimento. O primeiro indivíduo utilizou o aparelho Herbst como opção terapêutica e o outro foi tratado com osteotomia mandibular sagital bilateral. Foram avaliados os resultados cefalométricos, oclusão e face desses indivíduos. A correção da Classe II para uma oclusão normal tratada com sobressaliência horizontal e vertical corretas ocorreu tanto no caso tratado com aparelho Herbst quanto no associado à cirurgia de avanço mandibular. Assim, conclui-se que o aparelho Herbst pode ser uma alternativa para correção da má oclusão em casos limítrofes do Padrão II deficiência mandibular, Classe II, divisão 1, em adultos.
Herbst appliance X mandibular sagittal split osteotomy in adult class II, division 1 treatment: case reports
Keywords: Orthodontics; Malocclusion; Angle Class II; Sagittal split ramus osteotomy; Ortodontia; Má oclusão de Angle Classe II; Osteotomia sagital do ramo mandibular